Utilization of Teacher Supervision Tool in Influencing Teacher Effectiveness in Secondary Schools in Rukungiri District – Uganda - Evans, Tayebwa (Kabale University, 2022)
Dissertation Submitted to the Directorate of Graduate Studies in Partial Fulfillment of the Requirements for the Award of Degree of Master of Arts in Education Management of Kabale University